Increased serum levels of anti-ganglioside M1 auto-antibodies in autistic children: relation to the disease severity - Mostafa, Gehan A (BioMed Central, 2011)
BACKGROUND: Autoimmunity to the central nervous system (CNS) may play a pathogenic role in a subgroup of patients with autism. This study aimed to investigate the frequency of serum anti-ganglioside M1 auto-antibodies, as indicators of the presence of autoimmunity to CNS, in a group of autistic children. We are the first to measure the relationship between these antibodies and the degree of the severity of autism. METHODS: Serum anti-ganglioside M1 antibodies were measured, by ELISA, in 54 autistic children, aged between 4 and 12 years, in comparison to 54 healthy-matched children. Autistic severity was assessed by using the Childhood Autism Rating Scale (CARS). RESULTS: Autistic children had significantly higher serum levels of anti-ganglioside M1 antibodies than healthy children (P < 0.001). The seropositivity of anti-ganglioside M1 antibodies was found in 74% (40/54) of autistic children. Serum levels of anti-ganglioside M1 antibodies were significantly higher in autistic children with severe autism (63%) than those with mild to moderate autism (37%), P = 0.001. Moreover, serum anti-ganglioside M1 antibodies had significant positive correlations with CARS (P < 0.001). CONCLUSIONS: Serum levels of anti-ganglioside M1 antibodies were increased in many autistic children. Also, their levels had significant positive correlations with the degree of the severity of autism. Thus, autism may be, in part, one of the pediatric autoimmune neuropsychiatric disorders. Further wide-scale studies are warranted to shed light on the possible etiopathogenic role of anti-ganglioside M1 auto-antibodies in autism. The role of immunotherapy in autistic patients who have increased serum levels of anti-ganglioside M1 antibodies should also be studied.